Technology integration for meaningful classroom use a standards-based approach - Cennamo, Katherine; Ross, John.D; Ertmer, Peggy A. (Wadsworth. Cencage Learning, 2014)
Updated and streamlined for easier use, Technology integration for meaningful classroom use: s standards-based approach, 2nd ed., equips readers with the knowledge, creative and critical thinking skills, and confidence needed to become "self-directed learners" who can successfully navigate the constantly changing environment of technology integration in the classroom. Using the principles of self-directed learning as its foundation, the book aims to help readers learn to evaluate and reflect on professional practice to make informed decisions regarding the use of technology in support of student learning. The first educational technology book organized around the 2008 National Educational Technology Standards for Teachers (NETS-T) developed by the International Society for Technology in Education (ISTE), this standards-based approach provides the framework for developing, modeling, and teaching the skills and knowledge necessary for integrating technology in authentic teaching and learning. An end-of-book supplement provides examples of technology integration in practice within specific content areas, guided by the national standards that apply to each content domain. -- publisher. Thoroughly updated and streamlined for ease of use